Discourses of incarnational belonging: Unpacking the motivations and goals of white urban relocators. Issue 4 (7th August 2020) - Eccleston, Sara M. Perisho
ABSTRACT: This study critically examines the racial dynamics of Christian community development efforts. I use the Christian Community Development Association's (CCDA) practice of relocation (the process by which middle to upper-income individuals intentionally relocate to low-income neighborhoods for community partnership) as my entry-point to this discussion. The intent of this project is twofold: First, I build on current literature of relocation by contextualizing the CCDA within broader historical trends; Second, I ground my study within critical race and whiteness studies, in order to consider how racial power and inequality remain, despite good intentions, entrenched in community development efforts for proximity, belonging, and solidarity. My findings suggest that as participants sought to become a vested member of their geographic community, they drew upon discourses that tended to minimize issues of power and difference, implicitly positioned themselves in redemptive roles, and de-emphasized historical structures of discrimination.